Fitness for work in employeers exposed to ionizing radiations with an increased susceptibility to malignancies - Malesani, Fabio; Guglielmi, Giovanni (La Medicina del Lavoro, 2017)
Background: The assessment of fitness for work regarding employees exposed to ionizing radiations and with an increased susceptibility to malignancies requires a particularly complex procedure. Objectives: To determine, where possible, parameters for the assessment of fitness for work of employees exposed to ionizing radiations, who have increased susceptibility to malignancies. Methods: To set out suitable criteria for the assessment of fitness for work. Results: Existing laws, technical standards, scientific literature and publications issued by international organizations and dealing with the health and safety of workers exposed to radiations may help establish criteria to inform assessment of fitness for work. Conclusions: Taking into account the concept of acceptable risk, the application of objective criteria as well as of subjective considerations may allow professionals to make individualised assessments of fitness for work.